Efektifitas Antibiotik Klindamicin Terhadap Bakteri Propionibacterium Acnes Dengan Metode Difusi Pada Pasien Acne Vulgaris - Muhamad Syafei Hamzah; Arief Effendi; Eka Silvia; Anggunan; Ade Utia; Zulhafiz Mandala; Marina Ayu Ningsri; Alvin Andrian Susanto; Muhammad Kevin Wiratama (Medula, 2022)
Acne vulgaris (AV) is defined as a skin disease caused by chronic inflammation of the pilosebaceous unit consisting of non-inflammatory lesions such as open comedones and closed comedones with inflammatory lesions in the form of papules, pustules, and nodules. Tetracycline has a very strong inhibitory power against Propionibacterium acne bacteria. This study aims to compare the effectiveness of the antibiotics clindamycin, benzoyl peroxide, erythromycin, azelac acid and Lactobacillus achidopillus with the effectiveness of tetracycline against Propionibacterium acnes. Research on the effectiveness of tetracycline antibiotics against Propionibacterium acnes was carried out in vitro using the disc diffusion method on Mueller-Hinton Agar media and analyzed the data using Shapiro-wilk for data normality. After being declared to be normally distributed (p>0.05), an unpaired T-test was performed. If the data obtained were not normally distributed, the Mann-Whitney test was performed to test the ratio 1 and 2. The mean effectiveness of tetracycline antibiotics was 48.7 mm and placebo/ vaseline of 0 mm against Propionibacterium acnes in vitro. Based on the unpaired T-Test, Sig.(2-Tailed) = 0.000 (p<0.05) was obtained, which means that there is a significant difference in each variable. There are differences in the effectiveness of Tetracycline antibiotics with placebo/vaseline on the growth of Propionibacterium acnes using the in vitro diffusion method.